Bayesian estimation of NIG-parameters by Markov Chain Monte Carlo Methods - Jostein Lillestøl (Humboldt University of Berlin, Interdisciplinary Research Project 373: Quantification and Simulation of Economic Processes, 2000)
The Normal Inverse Gaussian (NIG) distribution recently introduced by Barndorff-Nielsen (1997) is a promising alternative for modelling financial data exhibiting skewness and fat tails. In this paper we explore the Bayesian estimation of NIG-parameters by Markov Chain Monte Carlo Methods.
urn:nbn:de:kobv:11-10048384
Keywords: 330; Normal Inverse Gaussian distribution; Bayesian Analysis; Markov Chain Monte Carlo